The Urgency of Islamic Character Education to Anticipate Bullying Behavior in Boarding Schools - Akhmad Ramli; Irsyad Dhahri; Moh Solehuddin; St Rahmah; Muhammad Haris; Fatimah Malini Lubis (At-Ta'dib, 2023)
Islamic character education plays a vital role in mitigating bullying behavior within boarding schools by fostering student behavior characterized by politeness, tolerance, and respect for differences. This study aims to analyze the significance of Islamic character education in proactively addressing bullying behavior in boarding schools through a literature review methodology. Employing a qualitative approach, the research utilizes a literature review analysis technique to gather data from various sources, including books, journal articles, and research findings related to Islamic character education and bullying in schools. The collected data is analyzed using content analysis techniques. The findings of the study indicate a pronounced urgency for implementing Islamic character education in anticipation of bullying behavior in boarding schools. Islamic character education not only shapes students' behavior to be polite, tolerant, and respectful of differences but also enhances their empathy, concern, and courage to combat bullying. Consequently, boarding schools should reinforce Islamic character education within their curriculum and integrate it into daily school activities. In conclusion, this study underscores the paramount importance of Islamic character education in preventing bullying behavior in boarding schools. Hence, it is imperative that Islamic character education becomes an integral component of the educational curriculum in boarding schools, fostering positive student behavior and reducing instances of bullying.